Identifying Rewards Over Difficulties Buffers the Impact of Time in COVID-19 Lockdown for Parents in Australia - Herbert, Jane S.; Mitchell, Annaleise; Brentnall, Stuart J.; Bird, Amy L. (Frontiers in Psychology, 2020)
Objective: Physical isolation measures, known as lockdown or shelter-in-place, experienced during coronavirus disease 2019 (COVID-19) have the potential to cause psychological distress. This study was conducted to examine parents’ perceived stress and whether reports of rewards and challenges during lockdown impacts stress. Methods: Data was collected using a cross-sectional online survey in New South Wales, Australia, across the 4-week lockdown. The survey was completed by 158 parents of children aged under 6 years. Stress was measured using the short form of the Perceived Stress Scale (PSS-4). Rewards and challenges were reported in response to two open-ended questions. Results: There was a weak negative correlation between PSS-4 scores and days in isolation (r = -.167, p = .022), with parents who had spent longer in isolation reporting fewer stress symptoms. The relationship between time in isolation and stress was moderated by the degree to which parents described more rewards than challenges: parents who perceived high rewards and low challenges reported lower PSS-4 scores with more days in lockdown; whereas parents who perceived low rewards and high challenges reported higher PSS-4 scores with more days in lockdown. The moderation model examining associations between time in isolation and rewards ratio explained 13% of the variance in PSS-4 scores. Conclusions: Lockdowns are not uniformly or consistently negative experiences for parents. Identifying positive aspects of the experience may serve to buffer negative mental health risks across time. Understanding resilience strategies is critical for supporting current psychological well-being, and to adequately prepare for future pandemic experiences.